Línea base ambiental y expectativas sociales y económicas de la población de comunidades de la etnia Chapra de la quebrada Pushaga, Río Morona.2024 - Vargas Gonzales, Cinthya Maite (2024)
The research was carried out in communities of the Chapra ethnic group, in the Morona district. It is a non-experimental, observational-descriptive, analytical, cross sectional quantitative study. A structured interview was applied to the leaders of the Chapra Autonomous Government and to the Apu of the communities. The reliability of the Cronbach's Alpha instrument is 0.82. The results of the environmental baseline of the abiotic and biotic environment show that the air remains pure and free of contaminants, and there are no strong winds. The rains are typically from the humid rainforest, fluctuating between 2000 and 3000 mm annually. The annual temperature ranges from a minimum of 22°C to a maximum of 34°C. The soil does not present areas of erosion, salinity, poor drainage, or soil contamination by agrochemicals, but there are localized points of contamination by oil spills and runoff of ferrous material oxides. The water maintains its natural characteristics, there is no salinity, sedimentation processes, drought or scarcity, the presence of microorganisms such as bacteria, viruses and parasites is evident in the untreated water consumed by the population, the presence of agrochemicals is not reported. The water has no odor, turbidity, it is sewage from streams. On the biotic medium there are species of flora in danger of extinction such as Mahogany (Swietenia spp.) Aguaje palm (Mauritia flexuosa). The area contains a high diversity of natural vegetation, timber species, fruit trees, medicinal and aromatic species of economic importance. There is a high diversity of terrestrial, poultry and aquaculture fauna species, some of them in danger of extinction, species of economic importance valued for their meat and commercial potential. In relation to the risk and vulnerability analysis of the area, no history of natural disasters is reported, there are no areas with instability or geological faults, landslide zones, landslides and mudslides. The presence of cold snaps and their effect on the increase in bronchial diseases are evident. There is no risk of droughts, but there are longer periods of absence of rain. In relation to anthropogenic processes, there is evidence of the risk associated with oil spills, deforestation due to extractive activities and migratory agriculture, illegal low-intensity alluvial mining, which negatively affects people's health and causes an increase in the foreign population, and the emergence in recent years of social conflicts that are multifaceted and can arise from territorial disputes.